"Everywhere You Look, You'll Find Food": Emerging Adult Perspectives Toward the Food Media Landscape. Issue 3 (4th May 2022) - Decorte, Paulien; Cuykx, Isabelle; Teunissen, Lauranna; Poels, Karolien; Smits, Tim; Pabian, Sara; van Royen, Kathleen; De Backer, Charlotte
ABSTRACT: This study explores what emerging adults value in food media, i.e. food-focused content and personae in media. Emerging adults (18–25) are an important target group for food media as they transition toward nutritional independence and consume media substantially. Seven semi-structured focus groups were conducted with thirty-seven Belgian participants. Thematic analysis revealed three themes ( hedonism, ability, information ) grouping nine subthemes ( entertainment, sensory appeal, convenience, familiarity, cost, autonomy, education, health and fitness, and innovation ) characterizing emerging adults' food media experiences. Incidental exposure and interpersonal influences also mark their food media consumption. This demonstrates food media's interwovenness in emerging adults' media habits. Further research should consider these themes and complexities, including their potential impact toward food-related habits and media use.